Purging Contempt: Eliminating the Distinction between Civil and Criminal Contempt - Paul A. Grote (Washington University Law Review, 2011)
The Article examines the current state of the law of contempt on state and federal law in the U.S. in 2011. It presents an overview of the law of contempt and major developments of jurisprudence in the Supreme Court that impact the distinction between criminal and civil contempt. It discusses the International Union, United Mine Workers v. Bagwell, a case in the Supreme Court on the distinction between criminal and civil contempt.
Keywords: International Union; UMW v. Bagwell 512 U.S. 821 (1994); Contempt of court; Judicial power; United States